2020
DOI: 10.26444/aaem/110480
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity patterns in third trimester of pregnancy – use of pregnancy physical activity questionnaire in Poland

Abstract: Introduction. Adverse pregnancy outcomes are less common among physically active women, and children born to such mothers are less likely to be at risk for macrosomia, obesity and metabolic diseases in the future. Objectives. The aims of the study were to establish physical activity (PA) patterns among pregnant women in the third trimester, and to determine the attitudes of prenatal care providers to maternal PA during pregnancy. Materials and method. The study was conducted in 2017 using surveys from the Poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 30 publications
2
20
1
Order By: Relevance
“…We furthermore noted that in each study group, out of all types of activity, participants spent the most energy on household activities. Similar results were also obtained in other studies [ 30 , 47 , 48 , 49 , 50 ]. Based on our results of the linear regression analysis, it can be seen that regardless of coexisting factors, pregnant women significantly reduced activities related to movement during the early stage of the pandemic.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We furthermore noted that in each study group, out of all types of activity, participants spent the most energy on household activities. Similar results were also obtained in other studies [ 30 , 47 , 48 , 49 , 50 ]. Based on our results of the linear regression analysis, it can be seen that regardless of coexisting factors, pregnant women significantly reduced activities related to movement during the early stage of the pandemic.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we showed that women who gave birth in any period of the pandemic spent less energy on total physical activity in the third trimester of pregnancy (prepandemic Me: 170.7, Q1–Q3: 114.1–234.6 MET; COVID 1 group Me: 150.8, Q1–Q3: 103.0–229.5 MET; and COVID 2 group Me: 146.5, Q1–Q3: 95.1–202.6 MET). For comparison, in a study conducted in 2017 which also considered Polish women in the third trimester of pregnancy, the median energy expenditure for total physical activity was 196.9 MET (Q1–Q3: 137.1–268.9 MET) [ 47 ]. In turn, Krzepota el at.…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that physical activity be encouraged among pregnant women during antenatal care. Low-intensity physical activity was the study's most common form of physical activity, a finding corroborated by several researchers [34][35][36][37][38] as physical activity usually declines during pregnancy [36,39]. Hence, a light-intensity activity like walking (< 3.0 METs) is better than no activity.…”
Section: Plos Global Public Healthmentioning
confidence: 53%
“…The Mann-Whitney-Wilcoxon test was used to compare groups in relation to physical activity. The detailed methodology of the Pol-PrAMS study and the use of PPAQ has been presented in separate studies [8,9].…”
Section: Methodsmentioning
confidence: 99%